Music theory and analysis: 1450-1650 - Ceulemans, Anne-Emmanuelle; Blackburn, Bonnie J. (Louvain Université catholique de Louvain, 2001)
A conference on 'Music Theory and Analysis, 1450-1650' will take placefrom 23 to 25 September 1999 at the Université catholique de Louvain atLouvain-la-Neuve (Belgium). Its purpose is to bring together musicologistsinterested in the theory and analysis of Western music between 1450 and1650 and the interrelationship of the two disciplines.